Scientific Literacy: The Conceptual Framework Prevailing over the First Decade of the Twenty-First Century - António Costa; Manuel Loureiro; Maria Eduarda Ferreira (Universidad Pedagógica Nacional, 2021)
The term scientific literacy arises due to the need of the scientific community to see that the population validated its scientific and technological production. The construct Scientific literacy has been subject to diverse conceptual considerations over the years, arising from the scientific, technological, social and political changes that marked contemporary society characteristics. In this study, we sought to assess the evolution of the scientific literacy construct over the first decade of the twenty-first century, through qualitative research, using a bibliographic study. For the operationalization of this analysis, different dimensions for scientific literacy were defined. The results suggest that scientific literacy embodies a construct that is deictic in nature, shaped by the social, political, cultural and scientific contexts prevailing in the society it belongs to. The conclusion is that all of this conceptual matrix suggests a change in the relatively passive form in which science is appreciated of and the way this operates in society towards a commitment to personal involvement with science and towards the valuation of the importance of scientific knowledge throughout life.